57.4k views
2 votes
Please help me please! I really need it! Thank you so much!!!!!!!!!!! Sorry Quality is really bad

Please help me please! I really need it! Thank you so much!!!!!!!!!!! Sorry Quality-example-1
User PaFi
by
4.6k points

1 Answer

3 votes

Answer:

7
(5)/(6)

Explanation:

- 2
(1)/(3) - ( - 10
(1)/(6) ) = - 2
(1)/(3) + 10
(1)/(6) = - 2
(2)/(6) + 10
(1)/(6) = ( 10 - 2 ) + (
(1)/(6) -
(2)/(6) ) = 8 -
(1)/(6) = 7 + (
(6)/(6) -
(1)/(6) ) = 7
(5)/(6)

User Hasib Samad
by
4.5k points